Marketing graduate employability: understanding the tensions between institutional practice and external messaging - Divan, A.; Knight, E.; Bennett, Dawn; Bell, K. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
© 2019, © 2019 Association for Tertiary Education Management and the LH Martin Institute for Tertiary Education Leadership and Management. Do the narratives of employability constructed by higher education institutions for marketing purposes differ from the conceptualisation and/or the realisation of employability within those institutions? The study reported here drew on interviews with 16 senior academic and student support staff who were tasked with developing student employability at one of nine institutions in Australia, Canada and the UK. We employed Holmes’ conceptions of employability as possessional, positional or processual to analyse how the interviewees conceptualised employability and the presentation of employability on the institutional websites. We found that most institutions’ employability marketing narratives were inconsistent with the institutional practice reported by staff. We explain this tension in the context of two competing characterisations of higher education: a university-student transaction view; and a learning view. We emphasise the need for internal and external narratives to align and advocate the need for engagement in a constructive and critical dialogue involving all stakeholders.